The Benefits of Implementing the Android-Based iDentist Application as an Alternative outside the Government's Public Health Service Program - Sudewa, I Gusti Ngurah Wisnu; Ellina, Agusta Dian; Nurwijayanti, Nurwijayanti; Wardani, Ratna; Indasah, Indasah (Budapest International Research and Critics University, 2022)
The purpose of this study to discuss about the benefits of implementing the android-based identist application as an alternative outside the government's public health service program. This type of research design is qualitative using case studies. This study involved 2 types of data sources, namely primary sources and secondary sources. In collecting data, the number of samples used is in the range of 4-10 informants to see if the data is regulated, if the sample is less than 10, it has reached the saturation point, then stop the search for samples. Data analysis techniques were carried out by means of data reduction, data presentation, and drawing conclusion. The research results show that implementation of the android-based iDentist application can provide information on dental and oral health so that it can provide accurate dental and oral care. Implementation of the android-based iDentist application can overcome public complaints so that it can speed up dental and oral care.